Live Internet measurements using Westwood+ TCP congestion control - R. Ferorelli; L.A. Grieco; S. Mascolo; G. Piscitelli; P. Camarda (Global Telecommunications Conference, 2002. GLOBECOM ’02. IEEE, 2002)
Westwood+ TCP is a sender-side only modification of the classic TCP that is based on end-to-end estimation of the bandwidth available to the connection in order to shrink adaptively the TCP congestion window and the slow start threshold after congestion. We report measurements obtained using Linux implementations of Westwood+, Westwood and Reno to FTP data over Internet connections spanning continental and intercontinental distances. In particular, we show that the bandwidth estimation algorithm employed by Westwood+ nicely tracks the available bandwidth, whereas the previous bandwidth estimation algorithm used by TCP Westwood fails to work in the real Internet due to ACK compression. Collected live Internet measurements also show that Westwood+ improves the goodput, from 10% to 46%, with respect to TCP Reno.
Keywords: Internet; Bandwidth; Testing; Feedback; Programmable control; Adaptive control; Phase estimation; Linux; Area measurement; LAN emulation